2019
DOI: 10.1002/adsc.201900359
|View full text |Cite
|
Sign up to set email alerts
|

Photoinduced Cascade Reaction of Tertiary Amines with Sulfonyl Azides: Synthesis of Amidine Derivatives

Abstract: A metal-free cascade reaction of tertiary amines with sulfonyl azides promoted by acridinium salts under blue light irradiation was developed and provided amidine derivatives in moderate to good yields. Enamine was generated from tertiary amine via single-electron transfer promoted by acridinium salts, and the following [3 + 2] cyclization with sulfonyl azide and CH 2 N 2 release afforded the desired products.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 40 publications
0
17
0
Order By: Relevance
“…19 On the other hand, Li and co-workers reported the cascade reaction of tertiary amines with sulfonyl azides in the presence of DEAD (diethyl azodicarboxylate) for the preparation of N-sulfonyl amidines. 20 Recently, photocatalyzed cross-coupling of arylsulfonyl azides with tertiary amines in the presence of eosin Y and acridinium salts have been reported by Zeng et al 21 and Pan et al 22 respectively. An electrochemical synthesis of N-sulfonyl amidines from aliphatic amines and sulfonyl azides has been reported by Wang, Du and Zah.…”
Section: Introductionmentioning
confidence: 99%
“…19 On the other hand, Li and co-workers reported the cascade reaction of tertiary amines with sulfonyl azides in the presence of DEAD (diethyl azodicarboxylate) for the preparation of N-sulfonyl amidines. 20 Recently, photocatalyzed cross-coupling of arylsulfonyl azides with tertiary amines in the presence of eosin Y and acridinium salts have been reported by Zeng et al 21 and Pan et al 22 respectively. An electrochemical synthesis of N-sulfonyl amidines from aliphatic amines and sulfonyl azides has been reported by Wang, Du and Zah.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been demonstrated that such SET process can be facilitated by the ruthenium catalyst without oxygen, due to the amount of 5a acquired in entry 2 that indicated most of 2a could be converted to the enamine intermediate 1a with the assistance of the ruthenium catalyst in the absence of oxygen. On the contrary, it seems that oxygen cannot promote the spontaneous formation of enamine 1a (entry 3), and the previously proposed aerobic photocatalysis pathway 7 seems to contribute little in this ruthenium-promoted visible-light induced imidation, since the yield of 5a indicated that most of 1a was engendered through the above anaerobic SET process even in aerobic environment (entry 1). According to the above observations, it could be concluded that oxygen might be unnecessary to the conversion from amine 2a to enamine 1a, while it might enhance the following cycloaddition and ring-opening decomposition process, comparing the yields of 4a in entries 1 and 2.…”
Section: Resultsmentioning
confidence: 91%
“…Furthermore, the spontaneity of this visible-light enabled imidation in the absence of oxygen and photocatalyst (entry 13, Table 1 ) attracted our attentions, for such observation suggested that an anaerobic pathways to realize this imidation probably coexist with the aerobic photoredox pathway proposed by Zeng and Pan, 7 where oxygen was proposed to serve a vital role in dehydrogenation. To gain more insights into the mechanistic picture, some control experiments were conducted, especially focusing on identification of byproducts generated along with the amidine product ( Table 4 ).…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…Tertiary amines were effectively coupled with sulfonyl azides to give amidine derivatives (Scheme 83). 86 SET to the excited photocatalyst would generate a tertiary amine radical cation. Subsequent hydrogen radical abstraction by an oxygen radical anion and a double bond shift results in the formation of an enamine intermediate.…”
Section: Scheme 82 Double Functionalization Of Arenesmentioning
confidence: 99%